Functional Impairments and Rehabilitation Outcomes of Patients With Immunotherapy-Induced Acute Inflammatory Demyelinating Polyradiculoneuropathy, Myasthenia Gravis, and Myositis. (14th October 2021) - Ng, Amy H.; Molinares, Diana M.; Guo, Ying; Fu, Jack; Bruera, Eduardo
Abstract : Supplemental digital content is available in the text. Abstract: Immunotherapy has led to a higher survival rate among different oncological disease groups but also associated with adverse-related events in multiple organ systems. Immunotherapy-related musculoskeletal weakness often results in a loss of cancer survivors' physical function, ultimately impacting their independence and quality of life. This is a retrospective study of 24 cancer patients who were treated with immunotherapy either alone or in conjunction with other oncological treatments. Twelve subjects (50%) were found to have acute inflammatory demyelinating polyradiculopathy/Guillain-Barré syndrome, six (25%) myositis, two (8%) myasthenia gravis, two (8%) diagnosis of myositis/myasthenia gravis, and one (4%) Guillain-Barré syndrome/myasthenia gravis combination. Physical therapy was provided in 91.7% of the cases, and physiatrist was involved in 54% of the cases. Almost half (45%) were discharged home, six (25%) to acute inpatient rehabilitation, two (8%) to subacute rehabilitation, three (12.5%) to hospice, and two (8%) died. The average length of hospital stay was 30 days, and eight patients (33%) readmitted within 3 mos. Our findings highlight the severity of functional impairments and the need for early rehabilitation interventions.